Chorioamniotic Separation Found on Obstetric Ultrasound and Perinatal Outcome - Carolina Bibbo; Sarah E. Little; Jad Bsat; Kris Ann Botka; Carol B. Benson; Julian N. Robinson (Thieme Medical Publishers, Inc., 2016)
Abstract Objective This study aims to evaluate pregnancy outcomes in patients with spontaneous and iatrogenic chorioamniotic separation diagnosed by ultrasound after 17 weeks. Methods This is a retrospective cohort study of women with a singleton pregnancy who were diagnosed with chorioamniotic separation (n = 106) after 17 weeks' gestation from January 2000 to January 2013. Patients with chorioamniotic separation were compared with a group of patients who had obstetric ultrasounds without a diagnosis of chorioamniotic separation. Those without chorioamniotic separation were matched (1:1) on gestational age on the date of the ultrasound ( ± 2 weeks) (n = 106). The primary outcome was preterm delivery (< 37 weeks). Secondary outcomes included intrauterine growth restriction, stillbirth, and neonatal morbidity. Results The rate of preterm delivery was significantly higher for those with chorioamniotic separation than for those without (57.5 vs. 17.1%, p < 0.0001). There were no significant differences in the rate of aneuploidy, intrauterine growth restriction, stillbirth, or neonatal demise. The rate of stillbirth was significantly higher among those with chorioamniotic separation diagnosed before 24 weeks as compared with those diagnosed after 24 weeks (9.7 vs. 0%, p = 0.03). Conclusions Chorioamniotic separation is associated with preterm delivery. If diagnosed before 24 weeks, the rate of stillbirth is significantly higher.